2013
DOI: 10.19177/jrd.v1e32013263-272
|View full text |Cite
|
Sign up to set email alerts
|

Sonic, ultrasonic and manual instruments in the control of periodontal disease: an in vitro evaluation

Abstract: The purpose of this study was evaluating the damage caused by root planning through different types of instrumentation. To perform it, 30 artificial teeth were selected from Prodens trademark, and their roots were divided in longitudinal sense and later included partly in blocks type IV plaster. Next they were submitted to three different types of root instrumentation: manual, sonic and ultrasonic. In each group 15 strokes apex coronary was carried out. After the analysis of root structures, they were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…In this process, damage to the adjacent tooth structure and soft tissue is an expected occurrence. Hand tools (sickle scaler and curettes) caused the minimum tooth damage in the current study, which was similar to the findings of Molina et al 14 and Spinks et al 18 Chan et al reported that flame-shaped diamond bur resulted in a significantly higher percentage of tooth damage compared to the other two experimented methods, indicating that burs are inherently rigid instruments which can access both the gingival and interproximal areas. 20 An evident property in all of the study groups was a deficiency in restoration margins, in the form of gap and void.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this process, damage to the adjacent tooth structure and soft tissue is an expected occurrence. Hand tools (sickle scaler and curettes) caused the minimum tooth damage in the current study, which was similar to the findings of Molina et al 14 and Spinks et al 18 Chan et al reported that flame-shaped diamond bur resulted in a significantly higher percentage of tooth damage compared to the other two experimented methods, indicating that burs are inherently rigid instruments which can access both the gingival and interproximal areas. 20 An evident property in all of the study groups was a deficiency in restoration margins, in the form of gap and void.…”
Section: Discussionsupporting
confidence: 90%
“…As for sickle scaler, however, it was 15 minutes. 14 Then, an explorer was used to evaluate the overhang removal efficacy, which was defined as follows: • Score 0: Complete overhang removal • Score 1: Amalgam remaining in cavosurface Afterward, the operation area was photographed with a SONY camera; model DSC-W570/16.1 M.P (Tokyo, Japan). A stereo microscope (model: LX-4 SZX7, Olympus, JAPAN) with a magnification of ×10 was used to conduct a more accurate evaluation of the samples in terms of surface smoothness, tooth damage, the gap in the tooth and restoration interface.…”
Section: Methodsmentioning
confidence: 99%
“…The aims of periodontal therapy include removal of the dental biofilm, dental calculus and bacterial toxins. Elimination of these deposits is achieved by scaling, which can be performed using hand instruments or an ultrasonic device . Of late, ultrasonic scalers are commonly being used because they require less time for scaling compared to hand instruments, increase working efficiency by decreasing the chair time for patients and offer ergonomic benefits to clinicians .…”
Section: Introductionmentioning
confidence: 99%